Determinants driving the evolution of new multiple sclerosis lesions into chronic active or remyelinated states - G. Boffa; C. Razzetta; D. Boccia; S. Garbarino; E. Cipriano; A. Uccelli; C. Lapucci; M. Piana; M. Inglese (NeuroImage: Clinical)
Introduction: Once formed, focal lesions that develop in patients with multiple sclerosis (MS) can follow different trajectories. We aimed at identifying early clinical and MRI features associated with the evolution of new MS lesions into chronic-active versus remyelinated states. Methods: New contrast-enhancing (CE) lesions were classified after a 12-month follow-up with quantitative susceptibility mapping (QSM) into paramagnetic rim lesions (PRLs, representing chronic-active lesions) and isointense QSM lesions (ISO, representing remyelinated lesions). SHapley Additive exPlanations (SHAP) analysis, which highlights the most relevant features contributing to model predictions, was conducted using baseline clinical and MRI characteristics. A risk score was calculated for PRL and ISO classifications using the four most influential features for each task. Results: A total of 111 lesions from 44 MS patients were analyzed. At 12 months, 13 % lesions were classified as PRL and 45 % as ISO. The key predictive features were similar for both classes (lesion volume, patient age and sex) except for the pattern of contrast enhancement (which was selected for PRL classification) and lesion topography (which was selected for ISO classification). Older age (>48 years), male sex, bigger lesion volume (>5 mL) and the presence of a ring pattern of contrast enhancement favored PRLs, while younger age (<36 years), female sex, smaller lesion volume (<0.17 mL) and the juxta-subcortical/deep white matter location favored ISO. Interpretation: The outcome of a new MS lesion can be predicted at lesion onset considering few clinically accessible features.